Overview of Characteristics for Impaired Lung Function in Bentor Drivers in Gorontalo City in 2023 - Muhammad Fahran Darise; Sri Manovita Pateda; Yancy Lumentut; Abdi Dzul Ikram Hasanuddin; Muhammad Zukri Antuke (Universitas Negeri Gorontalo, 2023)
Introduction: Impaired lung function is a functional disorder of the lungs that causes a slowing of airflow during respiration. Bentor drivers are a profession with a risk of decreasing lung function due to work activities that are always on the road and exposed to motor vehicle pollution. Exposure to cigarette smoke in active and passive smokers is also significant in causing several other respiratory diseases, such as chronic obstructive pulmonary disease (COPD). The purpose of this study was to describe the risk factors for impaired lung function in Bentor drivers in Gorontalo City in 2023.Method: The research was conducted in June 2023 on eligible Bentor drivers accidentally found in Gorontalo City. The research instrument used a questionnaire, stress perception scale (SPS), and spirometry.Results: The results obtained are the distribution of risk factors for impaired lung function in Bentor drivers in Gorontalo City in 2023, based on length of work found more work more than five years (63.33%), more work more than 8 hours a day (75%), had smoking habits with a smoking duration of more than ten years (58.3%) and smoked more than ten cigarettes a day (62.5%) and had a severe perception of stress (66.6%).Conclusion: Bentor drivers are one of the contributing factors in impaired lung function. There is a relationship between the risk factors for smoking, length of work, duration of exposure to pollution, and perception of stress with lung function in Bentor drivers in Gorontalo City. Key words: Bentor drivers, lung function, smoking, stress perception